Os processos de comunicação da rede de lojas C&A e a construção do discurso em torno da moda acessível - Messias, Elizete Menezes (2015)
This research aims to analyze the communication and marketing strategies driven by C&A popular stores chain in order to ensure its commitment as a retailer that sells the best fashion for fair prices. Thus, we will examine the discursive processes concerned in the various C&A communicational disclosure materials, revealing the persuasion and seduction resources that these communication materials put into practice to spread values such as originality, exclusivity and good taste in the consumers minds. In parallel, this work investigates the emergence of new consumption patterns within the popular stores chain. We played here with the hypothesis that the marketing and communication actions spread values established on quality standards, aesthetics, innovation and femininity that reverberate current production and worldwide consumption of fashion images trends in order to position itself as a global fashion too. Methodologically, it is a bibliographic and documentary survey - gathering, organization and analysis of communication materials and campaigns and at the store - and consistent field research on the consumer processes observation that takes place at C&A. To do so, the work corpus consists of different communication materials arranged in stores, involving communication campaigns - catalogs, magazines produced by the retailer, posters, clothing labels, hangers and custom bags and manual operating instructions - the communication at the store - the visual merchandising and store windows - and the campaigns launching releases from 2010 to 2014. The research main theoretical and conceptual references involve a significant number of authors who appreciate the globalized contemporary fashion values, like Diana Crane, Gilles Lipovetsky, Guillaume Erner and Enrico Cietta. Relevance is given to this research, as there is a lack, among fashion communication studies in Brazil, of works about the messages proposed by popular chain stores, which are generally focused on high-end fashion brands